A theory of host country sentiments: An illustration in cross-border acquisitions - YIU, Daphne W. (Institutional Knowledge at Singapore Management University, 2024)
Capitalizing on massive sentiment diffusion and mobilization aided by mass media and social media nowadays, we introduce a general theory of host country sentiments to illuminate the granular, context-situated, and time dynamic power of social sentiments. We posit that host country is a value-laden context wherein a foreign entity’s strategic action stimulates host country stakeholders’ social sentiments and engagement in systems of discourses (“sentiment arousal”), mobilizes social sentiments toward the foreign entity (“sentiment competence”), and legitimizes social sentiments and the strategic action of the foreign entity (“sentiment resonance”). To test our theory, we employ a context of inward acquisitions by emerging market firms in an advanced economy, and postulate that host country sentiments toward objects of the inward acquisition (deal, acquirer, and inward investments from home country) will influence the likelihood of deal completion, an indication of host country legitimacy. We further highlight the patterns of host country sentiment dynamics, and showcase how sentiment volatility, wavelength, and augmentation exert heterogeneous effects on deal completion. Overall, we advocate a theory of host country sentiments in international management research that elucidates the interplay among host country sentiments, systems of social discourses, and multinational enterprise strategic outcomes in a host country.